An anatomical comparative study of some histological changes of date palm (Phoenix dactylifera L.) callus contaminated with fungi - Ahmed, Alaa N.; Abass, Mohammed H (Basrah Journal Of Date Palm Research, 2024)
The results of the investigation of fungi contaminating date palm tissue cultures revealed the isolation of 33 fungal species belonging to 14 genera with five sterile mycelia, which were diagnosed based on morphological and microscopic characteristics. Results of the anatomical study showed the presence of significant differences in the characteristics of bundle diameter and the number of tannin cells, with insignificant differences in the rest of the examined characteristics from the anatomical point of view of the callus of date palms of the healthy and contaminated Barhi cultivar. The results of the study also showed the effect of fungi on the tissues of the contaminated callus and the presence of degrading of the cell walls compared to the healthy callus.